Uso de corticóide antenatal em maternidades públicas brasileiras: prevalência e fatores associados - ARAÚJO, Hanna-Arony Wanderley Pereira de (2013)
Introduction: The administration of corticosteroids to pregnant women can prevent and modify the course of respiratory distress syndrome, enhance the effects of surfactant therapy after birth and reduce the incidence of peri-intraventricular hemorrhage in the newborn. It is safe in women with premature rupture of membranes and pregnancy-related hypertensive disorders. Because of such benefits, according to the Ministry of Health of Brazil, antenatal corticosteroids should always be used in all pregnant women between 24 and 34 weeks gestation at risk for preterm delivery. Hence the importance of knowing the factors associated with failure to use the therapy in order to contribute to reducing neonatal mortality. Objectives: To determine the frequency of antenatal corticosteroid therapy in pregnant women with gestational age between 24 and 34 weeks in Brazilian public hospitals, and identify factors associated with non-use of this technology. Methods: We conducted a cross-sectional observational taking as the source database with collection performed from March 2004 to March 2005, which included 16 Brazilian public hospitals, with 1109 observations. Were included in the study infants with birth weights between 500 and 1,749 g. Categorical variables were described using percentages and analysis of differences between proportions was performed using the χ ² test - Mantel-Haenszel. To assess the factors associated with non-use of antenatal corticosteroids was used multivariate analysis of hierarchical type, classifying the variables into proximal, middle and distal in relation to the outcome. Results: the sample of 1,109 pregnant women with gestational age between 24 and 34 weeks, 528 (47.6%) did not use antenatal corticosteroids. Among the neonatal units studied, the incidence of non-use of antenatal corticosteroids ranging between 83.6% and 14.5%. Among the proximal variables, less complex hospital and absence of hypertension in pregnancy were associated with non-use of antenatal corticosteroids. Do not perform prenatal was the only intermediate variable analyzed that showed statistical significance for non-use of technology. Among the variables analyzed only the distal low education was associated with outcome. Conclusions: The study revealed a high frequency of non-use of antenatal corticosteroids for the period where technology is indicated, ie between 24 and 34 gestational weeks, which may point to the poor quality of hospital care for this condition units evaluated . The failure therapy use was associated with both the proximal variables such as intermediate and distal, revealing the multiplicity of interrelated factors to the outcome.